An Experimental Investigation on the Effect of Wind Speed on Cotton Combustion. (2018) - Wang, Zhi-sheng; Liu, Wan-fu; Ni, Zhao-peng; Wang, Lu; Gao, Bo
Abstract: Based on the fire safety of cotton, five groups of test samples were selected in the combustion experiment. Experiments were carried out under different wind speed conditions. The experimental results show that, as the wind speed increases, the phenomenon of flame combustion becomes more obvious and the mass loss rate is accelerated. According to the analysis of the same wind speed at different temperatures, it can be seen that the larger the wind speed is, the faster the combustion will spread from the surface of the specimen to the interior.